A Roadmap Draft for the Development of Marine Regenerative Medicine in I.R. Iran - Mahdi Mahmoudpour; Iraj Nabipour (Iranian South Medical Journal)
Background: Regenerative medicine is an emerging multidisciplinary branch of science that addresses the replacement, engineering, and re-engineering of cells, tissues or organs in order to establish or restore their normal functions. According to the basic concepts of regenerative medicine, marine regenerative medicine (MRM), inspired by marine organisms, can be defined as following the regenerative medicine strategies to develop regenerative medicine products for clinical applications. Materials and Methods: The common framework of the proposed convergence roadmap of the Albright Strategy Group, which consists of four steps, was used to develop the roadmap for the development of MRM in I.R. Iran. The first step is definition and scope of MRM; the second step shows the direction to MRM based on its structure and fundamental elements; the third step discloses the most competitive technologies in MRM; and the fourth step presents an investment summary and action plan for MRM in the I.R. Iran. Results: Five strategies may be considered for the development of MRM in I.R. Iran. 1. The establishment of a center of excellence for research in MRM in the south of Iran; 2. Networking and establishment of a common platform for MRM with the regenerative medicine community; 3. Establishing connections with industries and the world of business; 4. Educating and training the next generation of human resources to provide a critical national mass of workforce for MRM; 5. The development of biological models, tools and techniques of MRM. Conclusion: Since research on marine stem cells, whole body regeneration (WBR) of marine organisms, application of advanced biomaterials, and the principles of regenerative pharmacology are fundamental pillars for MRM, these structural elements should be considered in the roadmap draft of MRM in I.R. Iran.